"Attention, please" to situation: Replies to commentaries by Uleman, Matsumoto, Hamamura and Takemura, and Vignoles. Issue 4 (28th October 2018) - Takano, Yohtaro; Osaka, Eiko
Abstract : Takano and Osaka (2018) tested the validity of the common view that Japanese are more collectivistic than Americans by reviewing empirical studies published mainly during recent two decades, and found that this common view was not supported by most of the reviewed studies. All the four commentaries on this review of ours shared with us the basic judgment that the common view is untenable. In this reply, we present arguments to resolve some doubts cast on our review, and then argue that situation is a key concept to investigate critical issues related to individualism and collectivism such as their dimensionality and distinction between societal level and individual level cultural difference.